LOCATION OF FUNGI IN PUMKPIN SEED: Short Communication - Sultana, Nasreen (Biological Sciences - PJSIR, 2003)
Pumpkin (Cucurbita pepo L.) is an important and widely cultivated cucurbitaceous vegetable crop in Pakistan. Over forty-five seed-borne fungi have been reported to be associ ated with pumpkin seeds in Pakistan (Yunis & Kauser, 1966; Sheikh 1990; Sultana et al 1992; Ahmed et al 1993). Mac rophomina phaseolina, Botryodiplodia theobromae, Fusarium equiseti, F. semitectum, F. soJani and F oxysporum were found in high frequencies in cucurbits seed (Maholay